Epstein-Barr Virus BZLF1 Gene, a Switch from Latency to Lytic Infection, Is Expressed as an Immediate-Early Gene after Primary Infection of B Lymphocytes - Wen, Wangrong (American Society for Microbiology, 2007)
We demonstrate here that the Epstein-Barr virus (EBV) BZLF1 gene, a switch from latent infection to lytic infection, is expressed as early as 1.5 h after EBV infection in Burkitt's lymphoma-derived, EBV-negative Akata and Daudi cells and primary B lymphocytes. Since BZLF1 mRNA is expressed even when the cells are infected with EBV in the presence of anisomycin, an inhibitor of protein synthesis, its expression does not require prerequisite protein synthesis, indicating that BZLF1 is expressed as an immediate-early gene following primary EBV infection of B lymphocytes.